Automated Event-Triggered GUI Testing and Bug Reproduction for Non-Android Applications - Anit Thomas M; Chinchu Krishna S (School of Industrial and System Engineering, Telkom University, 2021)
Today’s mobile gadgets are seamlessly incorporating innovative features demanded by the users. Most often, the applications contain bugs or functionality issues reported by the customers. The developers are responsible for reproducing such reported bugs, which are written in natural languages. Reproducing bugs from bug reports make the bug resolution inefficient. Nowadays, various methods are adopted to reproduce crash reports for android applications. But bug reproduction for non-android applications is still a challenging task. This paper proposes a novel approach that is capable of doing bug reproduction from bug reports to help the developers to solve the functionality issues of non-android applications in an automated manner. This approach uses a UI tester called the GUI engine, which is an excel sheet. The use cases which are to be tested can be filled in the GUI engine. All the use cases are to be filled based on a particular syntax. For that purpose, the developer can make use of a set of yaml files containing all the GUI information for all the screens of the application under test. The use cases are executed in the GUI engine and conclusions are made based on the test result. The GUI engine displays two colors green and red showing the working and failing of GUI components of the application under test. So that the developer can easily identify the failing components and take actions accordingly. The test has been done with more than 1000 test cases for one region and the result shows that almost all GUI components work for this method except for animation. It has tested for software developed for US, Europe, and German regions. Also, the proposed method is found to be much faster and efficient than the existing as well as manual testing methods.